Coupled Dynamic Response Analysis of A Multi-Column Tension-Leg-Type Floating Wind Turbine - 赵永生 杨建民 何炎平 顾敏童 (China ocean engineering, 2016)
This paper presents a coupled dynamic response analysis of a multi-column tension-leg-type floating wind turbine（Wind Star TLP system） under normal operation and parked conditions. Wind-only load cases, wave-only load cases and combined wind and wave load cases were analyzed separately for the Wind Star TLP system to identify the dominant excitation loads. Comparisons between an NREL offshore 5-MW baseline wind turbine installed on land and the Wind Star TLP system were performed. Statistics of selected response variables in specified design load cases（DLCs） were obtained and analyzed. It is found that the proposed Wind Star TLP system has small dynamic responses to environmental loads and it thus has almost the same mean generator power output under operating conditions as the land-based system. The tension mooring system has a sufficient safety factor, and the minimum tendon tension is always positive in all selected DLCs. The ratio of ultimate load of the tower base fore-aft bending moment for the Wind Star TLP system versus the land-based system can be as high as 1.9 in all of the DLCs considered. These results will help elucidate the dynamic characteristics of the proposed Wind Star TLP system, identify the difference in load effect between it and land-based systems, and thus make relevant modifications to the initial design for the Wind Star TLP system.